Metabolic and Non-Metabolic Peripheral Neuropathy: Is there a Place for Therapeutic Apheresis? - Straube, Richard; Müller, Gregor; Voit-Bak, Karin; Tselmin, Sergey; Julius, Ulrich; Schatz, Ulrike; Rietzsch, Hannes; Reichmann, Heinz; Chrousos, George P.; Schürmann, Annette; Jarc, Luka; Ziemssen, Tjalf; Siepmann, Timo; Bornstein, Stefan R. (Hormone and Metabolic Research, 2019)
As the rate of obesity and the incidence of diabetes mellitus have been increasing, diabetic neuropathy has become the most common cause of peripheral neuropathy in developed countries. In addition, a variety of pathogenetically heterogeneous disorders can lead to impairment of the peripheral nervous system including amyloidosis, vitamin deficiencies, uremia and lipid disorders, alcohol abuse, autoimmune and infectious diseases as well as exposure to environmental toxins. We have noted that a combination of these disorders may aggravate the manifestations of peripheral diabetic neuropathy, an effect, which is most pronounced when metabolic and non-metabolic pathologies lead to cumulative damage. Current treatment options are limited and generally have unsatisfactory results in most patients. Therapeutic apheresis (INUSpherese®) allows the removal of metabolic, inflammatory, immunologic and environmental contributors to the disease process and may be an effective treatment option. We reviewed the developments in therapeutic apheresis for metabolic and non-metabolic peripheral neuropathy, including the current literature as well as data from our university diabetes center.
Keywords: apheresis; neuropathy; lipids